O perfil das vítimas de acidentes de trabalho do tipo acidentes de trajeto em Palmas, Tocantins - Sousa, Dayvid William de; Alves, Ada Betelli Cardoso; Silva, Nibsyan Cristina da; Pereira, Sara Priscilla Gabriel; Neves, Tiago Veloso (REVISTA CEREUS, 2023)
Objective: to identify the profile of victims of accidents at work such as commuting accidents in Palmas, Tocantins, from 2009 to 2019. Method: data from 1,734 victims of accidents at work such as commuting accidents notified between the years of 2009 and 2019, contained in the Notifiable Diseases Information System. Results: It was found that, of the total number of victims, 81.4% are male. 80.56% are brown people. 59.3% of individuals are aged between 20 - 39 years. 46.30% have a low level of education. Among the most affected occupations is the agricultural worker in general with 9.75% of cases. The most prevalent injury was fractures, with 74.16%. And in relation to the evolution of cases, permanent disability obtained a percentage of 14.9%. Conclusion: brown men, with low education, at a young age, with the occupation of agricultural workers in general and motorcyclists represent the main profile of victims of accidents at work such as commuting accidents in Palmas-TO during the period studied.